Persisting Cancer in Black Salve Treated Skin Lesions: Results of a Large 5 Year Retrospective Analysis of Australian Histopathology Specimens - Andrew Croaker MMed; Lei Liu PhD; Stephen P. Myers BMed, ND, PhD (Integrative Cancer Therapies, 2023)
Background: To date there has been minimal research on the use of black salve escharotics. Whether cancer persistence is a frequent finding in treatment areas, the types of lesion being treated by patients, whether rural patients are more likely to use black salve and whether current government prevention initiatives are succeeding are all issues needing investigation. Methods: This study was a large national retrospective black salve pathology case series from 2015 to 2019. Five private pathology companies with 1471 collection centers located in 5 of the 8 Australian states and Territories provided de-identified skin pathology report information where black salve treatment had been documented in the pathology request. Results: Over the 5-year period 409 patients had treated 475 lesions with black salve. Benign lesions were present at the treatment site in 18% of cases; persisting cancer was found in 34.2% of the remaining black salve treated areas. The majority of treatment areas were located on the head and neck. Black salve caused necrosis of normal tissue when treating benign lesions, refuting claims of cancer specificity. Likelihood of black salve use increased with rurality based on Modified Monash (MM) scores. Black salve use, despite regulatory efforts, appears to be increasing with specimen numbers more than doubling from 2015 to 2019. Conclusions: Patients undergoing histopathological assessment of black salve treatment areas have high rates of cancer persistence. Patients are applying black salve to benign lesions and lesions in cosmetically sensitive areas. Rural patients have higher proportional rates of black salve use. The increasing incidence of black salve pathology specimens suggests current Australian black salve public health initiatives are failing.